Combined Dietary Intake and Its Association With Pulmonary Function and Chronic Obstructive Pulmonary Disease Risk in Korean Adults: 2016-2018 Korea National Health and Nutrition Examination Survey - Seoyeon Park; Heejung Park (Clinical nutrition research, 2025)
Chronic obstructive pulmonary disease (COPD) is a major respiratory disorder characterized by irreversible airflow limitation. The role of diet in the prevention and management of COPD is receiving increasing attention. This study aimed to examine the association between the composite intake of vegetables, fruits, meat, and fish and pulmonary function as well as COPD prevalence in a representative sample of Korean adults aged ≥ 40 years using data from the 7th Korea National Health and Nutrition Examination Survey. Higher vegetable intake was associated with significantly better pulmonary function parameters, including forced vital capacity (p < 0.001), forced vital capacity percent predicted (p = 0.050), forced expiratory volume (FEV) in 1 second (FEV1; p < 0.001), FEV1 percent predicted (p = 0.038), FEV in 6 seconds (p < 0.001), and peak expiratory flow (p < 0.001). Furthermore, individuals with a high combined intake of vegetables, fruits, meat, and fish demonstrated a 0.261-fold lower COPD prevalence than those without such intake (p = 0.039). The dietary inflammatory index (DII) was significantly lower among participants without COPD than among those with COPD (mean DII = -3.6947, p = 0.002), indicating that a diet rich in anti-inflammatory nutrients can help reduce COPD risk. These findings suggest that vegetable consumption supports improved respiratory function, and a composite dietary pattern incorporating various food groups may help reduce the prevalence of COPD in the adult population.